HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN CITRA DIRI PADA REMAJA AKHIR - Tika Nurul Ramadhani; Flora Grace Putrianti (Universitas Sarjanawiyata Tamansiswa, 2014)
Abstract This Research target is to know the relations between self confidence with self image by adolescence. Subject research is active student of Psychology Faculty Sarjanawiyata Tamansiswa University of Yogyakarta beetwen 18-22 years old amounting to 90 people. Research method use the technique of Purposive Sampling.Data intake use the Scale self confidance and self image from Suryani(2009). Scale self confidance consisted of by 60 item and Self image consisted of by 56 item.Result of this research show the existence of correlation coefficient of equal to 0,236 with the level significant 0,025 (p<0,05). Its meaning is hypothesis expressing there is positive relation self confidance by self image. Effectiveness regress in research of equal to 5,6% its meaning self confidance of equal to 5,6% determined by Self image and 94,4% influenced by other factors. Keyword : Self confidence, Self image, Adolescence